Middle-to long-term outcome after medial patellofemoral ligament reconstruction with Insall's proximal realignment for patellar instability - Ryo Shimizu; Yoshio Sumen; Kazuki Sakaridani; Masaki Matsuura; Nobuo Adachi (Elsevier, 2019)
Background: Recently, medial patellofemoral ligament (MPFL) reconstruction has become a common, widely used procedure to treat patellar instability. However, few reports exist on the long-term outcome after MPFL reconstruction. We elucidated the middle- to long-term outcome after MPFL reconstruction with Insall's proximal realignment. Methods: From 1999 to 2012, 42 knees of 32 patients who underwent MPFL reconstruction with Insall's proximal realignment were reviewed with a minimum follow-up of five years. Patients who could visit our office and receive some designated examinations were included in this study. The re-dislocation rate and patellar apprehension sign postoperatively were evaluated. The Kujala score and Knee Injury and Osteoarthritis Outcome Score (KOOS) were calculated. We assessed the images using plane x-ray and magnetic resonance imaging (MRI). The tilting angle (TA), congruence angle (CA), and lateral shift ratio (LSR) on the plane x-ray were measured pre- and postoperatively and at final follow-up. Using MRI, osteochondral lesions at the patellofemoral joint were evaluated. Results: A total of 20 knees of 15 patients (two male, 13 female) who could visit our office were studied. The follow-up rate was 47.6%. The mean age at operation was 19.9 (11-41) years and mean follow-up was 123 (60-215) months. One knee (5.5%) had a history of postoperative subluxation, and five (25%) had a positive apprehension sign. The mean Kujala score significantly improved from 65.5 to 86.1 points (P < 0.05). The mean KOOS (symptom, pain, activities of daily living [ADL], sports, quality of life [QOL]) was 74.4, 92.4, 97.3, 84.1, and 73.2 points, respectively, at final follow-up. On the plane x-ray, patellofemoral alignment was improved postoperatively, and this improvement was maintained at final follow-up. On MRI, in five of 20 cases, the patellofemoral osteoarthritic change was observed at final follow-up. However, in four of these five knees with severe osteochondral lesions, osteochondral fixation or transplantation surgery had been performed. Only one of the remaining 15 knees had a patellofemoral osteoarthritic change observed at final follow-up. Conclusion: Middle- to long-term outcome after MPFL reconstruction with Insall's proximal realignment at our institution was evaluated, and good clinical results were observed. Most patients who did not have a severe cartilage lesion preoperatively did not develop osteoarthritic change.